Roles of Streptococcus mutans in human health: beyond dental caries - Fang, Yanke; Chen, Xin; Chu, Chun Hung; Yu, Ollie Yiru; He, Jinzhi; Li, Mingyun (Frontiers in Microbiology, 2024)
Streptococcus mutans (S. mutans) is the main pathogenic bacterium causing dental caries, and the modes in which its traits, such as acid production, acid tolerance, and adhesion that contribute to the dental caries process, has been clarified. However, a growing number of animal experiments and clinical revelations signify that these traits of S. mutans are not restricted to the detriment of dental tissues. These traits can assist S. mutans in evading the immune system within body fluids; they empower S. mutans to adhere not merely to the surface of teeth but also to other tissues such as vascular endothelium; they can additionally trigger inflammatory reactions and inflict damage on various organs, thereby leading to the occurrence of systemic diseases. These traits mostly originate from some correlative findings, lacking a comprehensive evaluation of the impact of S. mutans on systemic diseases. Therefore, this review mainly centers on the dissemination route of S. mutans: “Entering the blood circulation - Occurrence of tissue adhesion - Extensive possible proinflammatory mechanisms - Concentration in individual organs” and analyses the specific effects and possible mechanisms of S. mutans in systemic diseases such as cerebral hemorrhage, inflammatory bowel disease, tumors, and infective endocarditis that have been identified hitherto.